Serotonin Transporter (5-HTT) Gene Polymorphisms and Susceptibility to Chronic Periodontitis: A Case-Control Study - Wu, Lan; Deng, Tong; Wang, Chao-Yang; Ren, Xue-Qun; Wang, Yun-Yun; Zeng, Xian-Tao; Geng, Pei-Liang (Frontiers in Genetics, 2019)
Objective: The current study is aimed at exploring the relationship between chronic periodontitis and serotonin transporter (5-HTT) gene polymorphisms (rs6354 and rs12449783) in the Chinese Han population. Methods: This study included a total of 120 patients with chronic periodontitis and 125 healthy control subjects. The 5-HTT gene (rs6354 and rs12449783) was genotyped using oral mucosal tissue with a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Linkage disequilibrium was examined using Haploview. Genotype and allele frequencies were compared between the cases and controls using a χ2 test. Results: Genotype distribution of the 5-HTT gene polymorphisms rs6354 and rs12449783 in the control group conformed to Hardy–Weinberg equilibrium. The frequency of the AC genotype, the AC + CC genotype and C allele of the 5-HTT rs6354 polymorphism was higher in cases (P < 0.05) vs. the healthy control. The adjusted odds ratio (OR) was 1.910 (95%CI = 1.049–3.476) for the AC genotype, 2.026 (95%CI = 1.115–3.680) for the AC+CC genotype, and 1.875 for the C allele (95%CI = 1.089–3.228. Such an association was particularly strong in women for the AC genotype (OR = 2.167, 95%CI = 1.034–4.542). The genotype and allele frequencies of rs12449783 did not differ between the cases and controls. Haplotype C-C (rs6354-rs12449783) was also more frequent in the cases (OR = 2.372, 95%CI = 1.154–4.875, P = 0.016). Conclusion: Chronic periodontitis is associated with the 5-HTT gene rs6354 polymorphism, as well as rs6354/rs12449783 interaction.